Levitation force of Cu (nano) added MgB2 superconductor - Gangwar V.K.; Tripathi D.; Dey T.K. (My University, 2025)
The experimental results on the levitation force of bulk MgB2 added with Cu nano particles has been reported in field cooling (FC) condition. The samples are prepared by a solid state reaction method under argon atmosphere. The structural characterization reveals the dominance of MgB2 phase. Again randomly oriented hexagonal grains of MgB2 having anisotropic nature and average grain size ∼300 nm, are clearly visible in FESEM micrographs. The superconducting transition temperature (TC) measured from R-T data is found to be 38.7K for pristine MgB2 sample, while a decrease in the TC can be seen for Cu (nano) added samples. The levitation force of the prepared samples is measured using a Cryocooler based handmade setup in field cooling (FC) conditions at 20K, and the data is further used to calculate the maximum levitation force (FMLF) and maximum attractive force (FMAF) of investigated samples at different field cooling heights (HFC) at 20K. © 2018 Author(s).